Broad‐ and fine‐scale structure across the distribution of the relict dace (Relictus solitarius) in the Great Basin desert, USA. Issue 6 (30th March 2022) - Finger, Amanda J.; Benjamin, Alyssa; Crookshanks, Chris; Campbell, Matthew A.; Sağlam, İsmail K.
Abstract: The Relict Dace is a small cyprinid and the only species in its genus, Relictus . It is naturally distributed in four drainage basins of central Nevada ‐ Butte Valley, Ruby Valley, Steptoe Valley, and Goshute Valley. The species has experienced periods of isolation and connection within these four basins since the late Pliocene, with the last 100 years characterized by anthropogenic disturbance. To better inform conservation actions, we investigated range‐wide and intra‐basin genetic structure and diversity and conducted F st outlier tests using RAD‐sequencing. We found high levels of genetic structure and four main lineages on a broad scale corresponding primarily to geography, and on a very fine scale (<1 km) within drainage basins. Signatures of selection in the form of outlier loci were documented in multiple locations across the range. Our results provide baseline data for conservation efforts and highlight the degree of fine‐scale genetic structuring that may be present in fishes of the Great Basin that are now restricted to small, isolated habitats—particularly wetland complexes. We caution against assuming that geographic distance is a proxy for genetic similarity in Great Basin fishes, encourage thorough genetic sampling, and note that broad‐scale genetic surveys can overlook fine‐scale genetic structure.